Merger Reversal in St. Louis: Implementation and Implications. (March 2022) - Duncan, Daniel
While examples have been clearly attested in the literature, the reversal of a merger is an uncommon occurrence that apparently contradicts principles underlying sound change. Understanding the implications of merger reversal therefore requires understanding of their implementation: whether there was a full merger in the first place, what the phonetic path taken to separate the merger was, and whether there was a social motivation behind the reversal. I take this approach in a case study of the traditionalstart -north merger of St. Louis English, which has reversed in recent decades. I show that the merger was most likely a near merger, that the reversal was achieved by raisingnorth and frontingstart, and that the reversal, at least the raising ofnorth, was socially motivated. I argue that the data highlights the role of perceptual salience in reversing mergers and illustrates that merger reversal can at times be chain shift-like in appearance, if not execution.